2015
DOI: 10.1257/app.20120387
|View full text |Cite
|
Sign up to set email alerts
|

Political Parties and Labor-Market Outcomes: Evidence from US States

Abstract: This paper estimates the causal impact of the party allegiance (Republican or Democratic) of US governors on labor-market outcomes. I match gubernatorial elections with March Current Population Survey (CPS) data for income years 1977 to 2008. Using a regression discontinuity design, I find that Democratic governors cause an increase in the annual hours worked by blacks relative to whites, which leads to a reduction in the racial earnings gap between black and white workers. The results are consistent and robus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 31 publications
0
49
2
Order By: Relevance
“…Over the period 1951-2004, Chang et al (2009 found that growth rates of real per capita income and government spending tended to be higher with Democrat governors. Beland (2015) found a decrease in the annual earnings gap between whites and blacks under Democrat governors but not in weekly and hourly earnings.…”
Section: Introductionmentioning
confidence: 80%
“…Over the period 1951-2004, Chang et al (2009 found that growth rates of real per capita income and government spending tended to be higher with Democrat governors. Beland (2015) found a decrease in the annual earnings gap between whites and blacks under Democrat governors but not in weekly and hourly earnings.…”
Section: Introductionmentioning
confidence: 80%
“…We refer interested readers to Berry et al (1998) for more details on this index. Conservative ideology is correlated with less regulation of markets in general whereas progressive ideology is correlated with support for health-related regulations in particular (Beland, 2015). Unfortunately, the ideology data are only available through 2013.…”
Section: State-level Factorsmentioning
confidence: 99%
“…While re‐electable Democrats tend to increase income taxes, lame duck Democrats tend to decrease them. Beland () and Beland and Unel (), using RDD, find that minorities such as blacks and immigrants have better labor‐market outcomes under Democratic rather than Republican governors…”
Section: Role Of Governors and Related Literaturementioning
confidence: 99%
“…While re-electable Democrats tend to increase income taxes, lame duck Democrats tend to decrease them. Beland (2015) and Beland and Unel (2015a), using RDD, find that minorities such as blacks and immigrants have better labor-market outcomes under Democratic rather than Republican governors. 2 There are other studies investigating the partisan impact at other levels of government in the United States and in other countries.…”
Section: B Related Literaturementioning
confidence: 99%